Asset Pricing With Higher Co-Moments and CVaR: Evidence from Pakistan Stock Exchange - Arif, Unbreen; Sohail, Muhammad Tayyab (International Journal of Economics and Financial Issues, 2020)
The development of asset pricing model is attributed to Markowitz (1952) which initiated towards Modern Portfolio Theory (MPT). The whole concept of MPT based on normality of returns assumption but in emerging economies volatility of returns is an important issue and sometimes markets only behave in either bullish or bearish patterns. Moreover, the volatility cannot be attributed and explained by variance rather it can be a result of extreme events (profits / losses) referred to as none elliptical distributions of returns. The objective of this study is to incorporate additional dimensions of risk in Markowitz Mean-Variance framework through inclusions of skewness kurtosis and coherent risk measure CVaR to obtain optimal portfolio with PGP approach. The study analyzes the portfolio returns of Mean-Variance (MV), Mean Variance Skewness (MVS), Mean Variance Skewness Kurtosis (MVSK) & Mean CVaR Skewness Kurtosis (MCVaRSK) models by using selected stocks of KSE-100 index over the time period of 2009-2018. The empirical findings suggest that portfolio returns impacted through inclusion of higher moments and CVaR and generated higher returns over the benchmark portfolio. The results of study are immensely useful for the fund managers and investors for stocks selection and construction of alternative portfolios. Keywords: Portfolio optimization, Mean CVaR Skewness Kurtosis, Multi objective optimization, Pakistan JEL Classifications: C61, G10, G11 DOI: https://doi.org/10.32479/ijefi.10351